A Survey on Routing Protocols and Challenge of Holes in Wireless Sensor Networks - Khan, I.F.; Javed, M.Y. (2008 International Conference on Advanced Computer Theory and Engineering, 2008)
Extensive usage of wireless sensor networks is the reason of development of many routing protocols. In this paper, the working of few routing protocols has been discussed, which are energy aware and some of them also provide reliability in data transmission. Performance of various protocols has been presented through simulation results that have been reported by leading researchers for the purpose of their comparison. The challenges faced by wireless sensor networks are also discussed in the paper. These challenges (i.e. coverage holes, routing holes, jamming holes, black/sink holes and worm holes) effect the performance of routing protocols.